(ISC)2 CCSP certified cloud security professional : official study guide - Chapple, Mike, 1975-; Seidl, David, CISSP (Ascent Audio, 2023)
(ISC)2 CCSP Certified Cloud Security Professional Official Study Guide, 3rd Edition is your ultimate resource for the CCSP exam. As the only official study guide reviewed and endorsed by (ISC)2, this guide helps you prepare faster and smarter with the Sybex study tools that include pre-test assessments that show you what you know, and areas where you need further review. In this completely rewritten 3rd Edition, experienced cloud security professionals Mike Chapple and David Seidl use their extensive training and hands on skills to help you prepare for the CCSP exam. Objective maps, exercises, and chapter review questions help you gauge your progress along the way, and the Sybex interactive online learning environment includes access to a PDF glossary, hundreds of flashcards, and two complete practice exams. Covering all CCSP domains, this book walks you through Cloud Concepts, Architecture and Design, Cloud Data Security, Cloud Platform and Infrastructure Security, Cloud Application Security, Cloud Security Operations, and Legal, Risk, and Compliance with real-world scenarios to help you apply your skills along the way. The CCSP credential from (ISC)2 and the Cloud Security Alliance is designed to show employers that you have what it takes to keep their organization safe in the cloud. Learn the skills you need to be confident on exam day and beyond.